Influence of Boron on Initial Austenite Grain Size and Hot Deformation Behavior of Boron Microalloyed Steels - Yong-liang Gao; Xiang-xin Xue; He Yang (Crystals, 2015)
The initial austenite grain size of boron microalloyed steel with three different amounts of boron (20, 40, and 60 ppm) was investigated under different heating temperatures (1150, 1100, and 1050 °C), and hot compression tests of samples in a wide range of temperature (900–1100 °C) and strain rate (0.1–10 s−1) were conducted. It was found that the initial austenite grain size increases with increasing temperature and boron content. The flow stress decreased with increasing boron content at lower strain rates. The flow stress constitutive equation of hot deformation was developed for the experimental steels; results showed that boron addition has the trend to reduce the hot deformation activation energy. The characteristic points of the flow curves were analyzed. Results revealed that the peak and critical stress decreased in response to an increase of boron content. The work-hardening behavior of both steels was investigated, and it was found that boron addition can decrease the work-hardening rate when strained at lower strain rates. On the contrary, peak and critical strains increased as boron content increased, indicating that boron has the ability to delay the onset of dynamic recrystallization.